Análise da gestão dos resíduos de serviços de saúde da rede hospitalar do estado do Tocantins, Brasil - Pereira, Helca Oliveira (Universidade Federal do Tocantins, 2015)
The National Unified Health System faces many challenges, including how to manage its healthcare service waste (HSW). This study was performed in the mains reference public hospitals of Tocantins state, Brazil, aiming to discuss the current management of HSW, with special attention in the state implementation of Management Plan for Healthcare Service Waste (MPHSW), in management practices and necessary infrastructure, and integration between hospitals and Health State Secretary (SESAU-TO). The research was performed from period of June to July 2013 using systematic observation and structured interviews with responsible people for management of HSW in each center. Among 18 Tocantins State Hospital, 5 have PGRSS; and 10 places (55.5%) accepted to participate in this research. In this group are included those 5 which have the plan. However, among these 5 places, just 1 started its implementation process that is not monitored and do not have official responsible to operate. It was found that all hospitals have failures in their waste management. The HSW are sorted as infectious, common and sharp (standardized by the cleaning company), but is missing strict rules in sorting wastes, result of the lack of training, not enough dump and without correct identification. It is not promoted by HSH the interaction between these hospitals about management of HSW. It is considerate that hospitals located in countryside, in special the smallest hospitals were more prejudiced by the distance to SESAU-TO and communication researches as transports are poorer (deficient logistic). The conclusion is that PGRSS does not present improvements in management of HSW in these studied hospitals, because it have not been implemented, so that 10 hospitals have inadequate management for their wastes; SESAU-TO don’t promote management of HSW in their hospitals in an integrated manner in order to minimize up the lack of local infrastructure; the state sanitary and environmental supervision have not been collaborating to improve this situation, because these places are working normally despites they do not have environmental license and sanitary permission.